2012
DOI: 10.3892/ijo.2012.1592
|View full text |Cite
|
Sign up to set email alerts
|

Glioblastoma cell line-derived spheres in serum-containing medium versus serum-free medium: A comparison of cancer stem cell properties

Abstract: In addition to the primary culturing of cancer stem cells (CSCs) from tumor tissues, CSCs are found in established tumor cell lines. However, it is unclear how culture conditions affect CSC enrichment. Additionally, the differentiation potential of cell line-derived CSCs has not been well studied. In our study, the glioblastoma cell lines LN229, T98G, U251n and U87, were cultured as spheres in serum-containing medium (serum spheres) or serum-free medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
61
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(70 citation statements)
references
References 35 publications
8
61
1
Order By: Relevance
“…In this study, the neurospheres isolated from glioblastoma cell line revealed the forementioned characteristics of GSCs, for instance, the neurospheres could differentiate to astrocyte and neuron, and isolated single cell from neurospheres could form subspheres. Our study is in compliance with the current reports [14,15].…”
Section: Discussionsupporting
confidence: 95%
“…In this study, the neurospheres isolated from glioblastoma cell line revealed the forementioned characteristics of GSCs, for instance, the neurospheres could differentiate to astrocyte and neuron, and isolated single cell from neurospheres could form subspheres. Our study is in compliance with the current reports [14,15].…”
Section: Discussionsupporting
confidence: 95%
“…A CSC fraction has been isolated in many cancers, including glioma [2][5], using various approaches [5][9]. Most glioma CSC have been derived from clinical tumor specimens [7], [10], [17] while only a few have been derived from established cell lines: Rat C6 cells and human malignant glioma cell lines (U373, A172, U87 and SU3) have been used [9], [17]–[23], [24].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, CD90 cell surface expression has been found to identify cancer stem cells in lung cancer cells [12]. Yan et al in their study on lung cancer cell lines (A549 and H446) found a high percentage of CD90 + cells in tumor sphere (41.2 %) which supports cancer stem cells [81] whereas CD90 was significantly low in non-tumorigenic adherent cells (0.9 %) [12]. CD90 + cells also expressed transcription factors Sox2 and Oct4 [12] which showed specific expression in metastasis promoting lung cancer stem cells [82,83].…”
Section: Cd90 As Marker For Malignant Cancer Cellsmentioning
confidence: 96%